Analisis Etika Peserta Didik Kelas X SMA Muhammadiyah 18 Sunggal Melalui Pembelajaran PAI - Ahmad Darlis; Hodi Alfian; Muhammad Musa Tarigan; Muhammad Diva Aldair Siregar (Peneliti.net, 2023)
The goals and ideals of the Indonesian nation are to realize the lives of citizens who have the nation's intellectual property listed in the 1945 Constitution, the government and citizens jointly solve educational problems so that a nation that is strong, independent and ready to face the world of globalization is formed. The world of education is currently experiencing the problem of fading the character of students, this can be observed especially in today's young generation. This article aims to find out the form of implementing Islamic-based character education at Muhammadiyah 18 Sunggal High School and find out what factors cause obstacles in efforts to implement forms of Islamic-based character education at Muhammadiyah 18 Sunggal High School. This research uses descriptive qualitative method. The data collection technique used was observation, interviews and documentation by observing directly in the field. Based on the results of data analysis, it can be found that the form of ethical analysis through PAI learning is in camping and MABIT (Faith Development and Taqwa Night) and extracurricular activities and through positive habituation activities to read the Koran and pray Dhuha in congregation as well as exemplary behavior. The inhibiting factors/obstacles of the school in the effort to implement character education at Muhammadiyah 18 Sunggal High School are facilities and infrastructure, students and teacher potential.